To Translate, or Not to Translate: A Cognitive Linguistic Analysis of Selected English and Polish Proverbs - Mandziuk-Nizińska, Justyna (Studia Anglica Posnaniensia, 2020)
Proverbs are often said to be part and parcel of the cultural, social, and cognitive heritage of a given linguistic community. This very specific nature of proverbs poses a challenge for any contrastive paremiological study which looks for “equivalents” in the target language. Especially difficult cases which escape systematic analysis are novel modifications of well-established traditional proverbs. To illustrate this, consider a proverb such as The early bird gets the worm. Based on this traditional saying, we have nowadays a number of modifications such as The early bird gets the worm, but the late one gets the pizza or The early bird gets the worm, but the second mouse gets the cheese. Also, a Polish original saying such as Kto rano wstaje, temu Pan Bóg daje, lit. “God provides to those who rise early”, now has a number of variants, including Kto rano wstaje, ten idzie po bułki (lit. “Those who rise early go to a shop to buy rolls”) or Kto rano wstaje, ten jest niewyspany (lit. “Those who rise early are sleepy”). One thing is certain: any attempt to develop a viable contrastive paremiological analysis can hardly ignore the complex and intricate relations between the cognitive, linguistic, and cultural aspects of proverbs compared. What is needed is a multifaceted account of such structures. A translation model which seems to be perfectly suited for this purpose is Lewandowska-Tomaszczyk’s theory of reconceptualization (2010). Using as a point of departure Lewandowska-Tomaszczyk’s assertion that that the translation of a proverb from a source language (SL) to a target language (TL) entails “a number of cycles of reconceptualization of the original SL message, expressed eventually in the TL” (2010: 107), we will offer a re-conceptualization-based account of the shift in meaning involving traditional proverbs and their jocular transformations.